2024
DOI: 10.3389/fcell.2024.1331074
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation in adult neural stem cells

Jiajia Shi,
Zilin Wang,
Zhijun Wang
et al.

Abstract: Neural stem cells (NSCs) exhibit self-renewing and multipotential properties. Adult NSCs are located in two neurogenic regions of adult brain: the ventricular-subventricular zone (V-SVZ) of the lateral ventricle and the subgranular zone of the dentate gyrus in the hippocampus. Maintenance and differentiation of adult NSCs are regulated by both intrinsic and extrinsic signals that may be integrated through expression of some key factors in the adult NSCs. A number of transcription factors have been shown to pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 148 publications
(167 reference statements)
0
1
0
Order By: Relevance
“…Since NSCs must be sustained from embryonic to adult stages to maintain life-long neurogenesis, the mechanism of sustaining NSCs into adulthood is crucial for neurogenesis in the adult brain. Recent research studies have shown the importance of histone modifications in controlling these processes to support adult neurogenesis [ 74 , 75 , 76 ]. In this section, we present examples of epigenetic mechanisms underlying the regulation of neurogenesis in the adult brain ( Figure 3 and Figure 4 ).…”
Section: Outline Of Adult Neurogenesis and Epigenetic Modificationsmentioning
confidence: 99%
“…Since NSCs must be sustained from embryonic to adult stages to maintain life-long neurogenesis, the mechanism of sustaining NSCs into adulthood is crucial for neurogenesis in the adult brain. Recent research studies have shown the importance of histone modifications in controlling these processes to support adult neurogenesis [ 74 , 75 , 76 ]. In this section, we present examples of epigenetic mechanisms underlying the regulation of neurogenesis in the adult brain ( Figure 3 and Figure 4 ).…”
Section: Outline Of Adult Neurogenesis and Epigenetic Modificationsmentioning
confidence: 99%